Host Invasion to Immune Evasion: Emerging Concepts in Pathogen Virulence Strategies - Alisha Arzoo (International Journal of Pathogens, 2025)
The interaction between hosts and pathogens represents a continuous evolutionary struggle, shaping both microbial virulence and host immunity. Pathogens employ diverse strategies to evade immune surveillance, ranging from antigenic variation and molecular mimicry to hijacking of host immune checkpoints. Simultaneously, hosts refine innate and adaptive immune mechanisms to counteract infection and limit damage. This reciprocal adaptation, known as host–pathogen coevolution, influences pathogen persistence, transmission, and fitness, while also sculpting immune system architecture. Case studies from viruses, such as HIV and influenza, bacteria like Mycobacterium tuberculosis and Staphylococcus aureus, and fungi including Candida albicans, illustrate the complexity of these dynamics. Clinically, immune evasion contributes to chronic infections, vaccine escape, and antimicrobial resistance, posing major challenges for healthcare systems. However, emerging therapeutic approaches, such as immune checkpoint modulation, quorum sensing inhibitors, and evolutionary-informed vaccine design, offer promising avenues to outpace microbial adaptation. Understanding coevolutionary principles is, therefore, critical not only for infectious disease management but also for anticipating future pathogen threats. This article reviews the mechanisms of host–pathogen coevolution, the clinical and evolutionary consequences of immune evasion, and the translational challenges in developing sustainable countermeasures
Keywords: Host–Pathogen coevolution; Pathogen fitness; antigenic variation; chronic infections; immune evasion